The Influence of Self-Efficacy and Work Stress on the Work Motivation of Civil Servant Teachers at SD Negeri 16, Delta Pawan District, Ketapang Regency - Nanda Destian; Arninda Arninda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the relationship between self-efficacy, work stress, and work motivation among civil servant teachers at SD Negeri 16 Delta Pawan, Ketapang District. Self-efficacy refers to an individual's belief in their ability to achieve specific results in certain situations. Work stress is the physical and emotional response to pressures from job demands that surpass an individual's capabilities. Work motivation is the force that drives individuals to accomplish their goals at work. The research employs an associative approach with a quantitative method. The data analysis reveals a connection between self-efficacy, work stress, and work motivation among civil servant teachers. Work stress has a more significant impact on work motivation than self-efficacy. However, when considered together, both factors play a vital role in influencing work motivation. These findings offer valuable insights into the factors that affect teachers' work motivation, emphasizing the need to develop strategies and policies that promote teachers' motivation and well-being at SD Negeri 16 Delta Pawan. Furthermore, this research contributes to the field of human resource management, providing a reference for researchers and practitioners to enhance the effectiveness of human resource management in educational institutions.